1987
DOI: 10.1111/j.1467-6494.1987.tb00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Fact and Fiction in Implicit Personality Theory

Abstract: This article reports two studies, where the accuracy of implicit personality theory (IPT) was investigated using on-line behavior counts as well as retrospective frequency estimates as standards of companson Eight discussion groups, each compnsmg six members, were videotaped Their act frequencies with respect to 16 types of behavior were judged on-line using two coding schemes, each one being applied by two independent raters Five other judges estimated the act frequencies retrospectively Furthermore, judges r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…It is more appropriate to include online records of behavior as a more dependable source of information about the actual relations, and to use these on-line records to evaluate the accuracy of both IPT and the correlations among personality ratings. I did this in an earlier study (Borkenau & Ostendorf, 1987b). The results of this study confirmed Jackson and Strieker's (1982) findings, thus corroborating the accuracy of IPT concerning the covariation among variables.…”
Section: Differences Between Implicit Personality Theory and The Strusupporting
confidence: 83%
See 1 more Smart Citation
“…It is more appropriate to include online records of behavior as a more dependable source of information about the actual relations, and to use these on-line records to evaluate the accuracy of both IPT and the correlations among personality ratings. I did this in an earlier study (Borkenau & Ostendorf, 1987b). The results of this study confirmed Jackson and Strieker's (1982) findings, thus corroborating the accuracy of IPT concerning the covariation among variables.…”
Section: Differences Between Implicit Personality Theory and The Strusupporting
confidence: 83%
“…If the covariations among personality variables are accurately perceived, however, IPT is unlikely to bias the correlations among personality ratings. Moreover, although base rates are hardly considered in the estimation of conditional likelihoods, the base rates themselves are accurately reported (Borkenau & Ostendorf, 1987b;Hasher & Zacks, 1984).…”
Section: Differences Between Implicit Personality Theory and The Strumentioning
confidence: 99%
“…In fact, it has been amply demonstrated (a) that high 'meaning overlap' of two trait adjectives goes together with high 'act overlap', i.e. with a high number of shared prototypical behavioural referents (Angleitner and Demtroder, 1988;Borkenau, 1986aBorkenau, , 1988Borkenau and Ostendorf, 1987), and (b) that estimated cooccurrence-probability of two traits and the correlation among memory-based ratings made for these traits are co-determined by the degree of 'act overlap' of both traits (Borkenau, 1986b(Borkenau, , 1988.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the theme within this literature is that when rating others (or even oneself), people will rely on their own implicit personality theories to infer what personality characteristics belong to a person. Other findings demonstrate that perceived personali-ty trait relationships might reflect actual relationships (e.g., Borkenau;Borkenau & Ostendorf, 1987), and thus suggest this ability as an adaptive tendency. Yet people can also be poor judges of co-variation (e.g., Alloy & Tabachnik, 1984;Berman & Kenny, 1976).…”
Section: Implicit Personality Theorymentioning
confidence: 93%